Estudio biosocial de una muestra de restos óseos provenientes de la colección osteológica de referencia de la Universidad de Antioquia (2014)
ABSTRACT: The aim of this paper is to explore pathological as well as traumatic injuries in a sample of 45 individuals from the Universidad de Antioquia’s human skeletal reference collection. Data was subsequently analyzed in combination with ofﬁcial contextual information on cause and manner of death in the city of Medellin from 2000 to 2005. Results from both sources showed correspondence, speciﬁcally those regarding mechanism of injury as well as certain diseases in speciﬁc age groups in the sample.